A Political academy in Paris, 1724-1731 - Childs, N (Voltaire Foundation, 2017)
The Entresol has been described as the most significant intellectual organisation in France in the first half of the eighteenth century. Its meetings in the 1720s were attented by some of the most important political thinkers in the country, among them Montesquieu, the marquis d’Argenson, the abbé de Saint-Pierre and the exiled lord Bolingbroke. The Entresol was a meeting of minds between older men who wished to keep in touch with current events, and younger men on their way up, who were eager to prove their suitability for high office in the French governing élite. Members came to meetings because they enjoyed talking about politics, especially foreign affais, and while the Entresol remained in favour, to be a member was a recommendation to those in government. In this book, the first to be published on the Entresol, Nick Childs examines the political thought and social background of the academy’s members, and the reason why their meetings were eventually banned. Illustrations Abbreviations Acknowledgements Preface I The membership and meetings of the Entresol II The political thought of the Entresol Appendix I Appendix II List of works cited Index